Memorandum of understanding between Universiti Teknologi MARA, Malaysia and Institut Seni Indonesia (ISI), Surakarta, Indonesia / Fakulti Muzik - Universiti Teknologi MARA, Fakulti Muzik (Universiti Teknologi MARA (UiTM), 2021)
uiTM and ISI will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.